Strategi Pengendalian Biaya melalui Efisiensi Anggaran Pemasaran dan Administrasi pada UMKM - Intan Anastasya Nainggolan; Gabriella Naomi Yaspis Siregar (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
This study aimed to analyze cost control strategies through the efficiency of marketing and administrative budgeting in Micro, Small, and Medium Enterprises (MSMEs). The main problem addressed was the ineffective budget management that led to cost inefficiencies and decreased business profitability. The research method used was a literature study by reviewing various relevant sources such as academic journals, books, and research reports related to MSME budgeting. The results showed that many MSMEs had not clearly separated marketing and administrative budgets, making it difficult to evaluate cost effectiveness. Several effective strategies identified included the utilization of information technology for marketing and administrative activities, improvement of financial literacy, implementation of flexible budgeting, digitalization of administrative systems, and better understanding of digital platform costs. In addition, regular operational audits played an important role in identifying inefficient expenditures. The study concluded that effective cost control could be achieved through the integration of proper budgeting planning, technology utilization, and continuous evaluation. By implementing these strategies, MSMEs were able to improve cost efficiency, maintain financial stability, and enhance competitiveness in an increasingly competitive market.